Student Management System of Bestlink College of the Philippines: Event Web Application: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The Event Management System consists of the planning of the entire event. It is also essentialfor all the students and professors to see the process of the whole event and have a schedule,time, place, upcoming event, and report of the upcoming activities. The event also has the incharge of the equipment like venues, chairs, lights, sound checks, and other equipment that isused for executing the entire event. It can also help the students to manage their schedulesfrom time to time, the place where the event was taking off, and organize the schedules andtime management. It is also essential for the professors to know about upcoming events fromother departments. The proper execution of the event will lead to success in executing theevent and a faster way to know and organize. In contrast to this, unattentively, students withtheir schedules are not organized and do not follow the rules and regulations of the event.The users of the Event Management System are the event organizer, event planner, students,and professors; it is limited only to the Bestlink College of the Philippines MV Campus, whichaims to execute and organize proper events. It can be seen or posted on the pages, socialmedia sites, and other systems used. It is essential for the event planner to know the requestor proposal of the event to start the plan immediately. The cost of event planning will be over amillion pesos, which is used for the equipment and tools used to build an event.There are many different things that might happen in an individual's life, but for them to all behelpful, they must all be planned out and carried out beforehand. A proper event managementsystem can aid in running events. A computerized system is therefore suggested to simplifythe event management procedure. The data flow chart aims to graphically represent themovement of the processes and the entity to which they belong to fully comprehend theprocesses and how they are carried out.
Keywords: IT & Management